ORGANIC INTELLECTUALS AND INORGANIC AGITATORS. SPAIN, ITALY AND FRANCE. 12TH CENTURY - Astarita Rojas, Carlos (Revista de Historia Social y de las Mentalidades, 2024)
Are studied here some of the agitators and intellectuals who perfomed in communal revolutions in the Middle Ages. Methodological considerations are made about the sources. With the chronicles speeches are analized. Also conditions under which the acted and they were educated.